In-vitro and In-silico Haemodynamic Analyses of a Novel Embedded Iliac Branch Device - Liang, Shichao; Jia, Heyue; Zhang, Xuehuan; Guo, Wei; Zhou, Guojing; Li, Shilong; Yuan, Panpan; Xiong, Jiang; Chen, Duanduan (Frontiers in Cardiovascular Medicine, 2022)
Background Iliac branch devices (IBDs) are valid tools for internal iliac artery preservation during endovascular abdominal aortic aneurysm and iliac aneurysm repair. The purpose of this study was to evaluate the effectiveness of a novel IBD with an embedded branch configuration. Method A typical iliac artery model was reconstructed, and two models were manufactured using three-dimensional printing technology. The novel IBD was deployed into one iliac artery model by an experienced vascular surgeon. A mock circulation loop (MCL) and a computational fluid dynamics (CFD) simulation were used to investigate the haemodynamic parameters of the iliac models without (Model A) and with (Model B) the IBD. A morphological analysis was conducted using computed tomography angiography and medical endoscopy. The flow distribution rate (FDR) and energy loss (EL) were used to quantify IBD performance. Results The FDR of the right internal iliac artery in the MCL of Model A and Model B was 18.88 ± 0.12% and 16.26 ± 0.09%, respectively (P = 0.0013). The FDR of the right internal iliac artery in the CFD simulation of Model A and Model B was 17.52 and 14.49%, respectively. The EL of Model A was greater than Model B in both the MCL and the CFD simulation. Compared with Model A, Model B had a larger region (8.46 vs. 3.64%) with a relative residence time of >20 Pa−1 at peak systole. Meanwhile, the area where the oscillatory flow index was >0.4 was significantly smaller in Model B than in Model A (0.46 vs. 0.043%). The region with an average wall shear stress of >4 Pa was greater in Model B than in Model A (0 vs. 0.22%). Conclusion The MCL and CFD simulation showed that the novel IBD had little impact on the FDR and EL of the iliac artery models. However, the IBD might be an effective tool for the treatment of abdominal aortic/iliac aneurysms that extend into branches. Further investigations are warranted to confirm whether this IBD could be useful in the clinic.